Upaya Guru Madrasah dalam Mengatasi Kesulitan Belajar Tajwid Al-Quran Siswa Kelas Takhassus MI Ar-Riyadh Bontang Tahun Pelajaran 2024/2025 - Robbani, Ahmad Mujaddid (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
This thesis discusses about The Efforts of Madrasah Teachers in Overcoming Learning Difficulties of Quranic Tajweed for Takhassus Class Students at MI Ar-Riyadh Bontang. The research aims to describe (1) The Efforts of Madrasah Teachers in Overcoming Learning Difficulties of Quranic Tajweed for Takhassus Class Students at MI Ar-Riyadh Bontang, and (2) Overcoming Learning Difficulties of Quranic Tajweed for Takhassus Class Students at MI Ar-Riyadh Bontang. This type of research is qualitative with data collection techniques using observation, interviews, and documentation. The subject of this research is the madrasah teacher at MI Ar-Riyadh Bontang. The results of this study indicate that: the efforts of madrasah teachers are (1) Forming a tahsin program, (2) Providing motivation, (3) Providing guidance, (4) Students practicing in front of friends, (5) Involving other parties such as regular class teachers and parents. To overcome learning difficulties in Quranic Tajweed for Takhassus class students, the madrasah teachers carry out (1) Teachers prepare a 3-month tahsin program at the beginning of the academic year, (2) Providing additional time for students who have difficulties in learning Quranic Tajweed, (3) Teachers use the talaqqi method and repetition, (4) Teachers provide special attention to Takhassus class students who have difficulties in learning Quranic Tajweed and give rewards to students who are able to practice learning Quranic Tajweed in reading the Quran. The Efforts of Madrasah Teachers in Overcoming Learning Difficulties of Quranic Tajweed have a very positive impact on improving the quality of Quranic Tajweed reading for Takhassus Class Students at MI Ar-Riyadh Bontang.